Hypoxia Induces Mitochondrial Defect That Promotes T Cell Exhaustion in Tumor Microenvironment Through MYC-Regulated Pathways - Liu, Yi-Na; Yang, Jie-Feng; Huang, Dai-Jia; Ni, Huan-He; Zhang, Chuan-Xia; Zhang, Lin; He, Jia; Gu, Jia-Mei; Chen, Hong-Xia; Mai, Hai-Qiang; Chen, Qiu-Yan; Zhang, Xiao-Shi; et al. (Frontiers in Immunology, 2020)
T cell exhaustion is an obstacle to immunotherapy for solid tumors. An understanding of the mechanism by which T cells develop this phenotype in solid tumors is needed. Here, hypoxia, a feature of the tumor microenvironment, causes T cell exhaustion (TExh) by inducing a mitochondrial defect. Upon exposure to hypoxia, activated T cells with a TExh phenotype are characterized by mitochondrial fragmentation, decreased ATP production, and decreased mitochondrial oxidative phosphorylation activity. The TExh phenotype is correlated with the downregulation of the mitochondrial fusion protein mitofusin 1 (MFN1) and upregulation of miR-24. Overexpression of miR-24 alters the transcription of many metabolism-related genes including its target genes MYC and fibroblast growth factor 11 (FGF11). Downregulation of MYC and FGF11 induces TExh differentiation, reduced ATP production and a loss of the mitochondrial mass in T cell receptor (TCR)-stimulated T cells. In addition, we determined that MYC regulates the transcription of FGF11 and MFN1. In nasopharyngeal carcinoma (NPC) tissues, the T cells exhibit an increased frequency of exhaustion and loss of mitochondrial mass. In addition, inhibition of miR-24 signaling decreases NPC xenograft growth in nude mice. Our findings reveal a mechanism for T cell exhaustion in the tumor environment and provide potential strategies that target mitochondrial metabolism for cancer immunotherapy.